July 2017 ENCALS statement on edaravone - Hardiman, Orla (My University, 2017)
Neurologists of the ENCALS centers throughout Europe have discussed the potential of edaravone as anew therapy for amyotrophic lateral sclerosis (ALS,Motor Neuron Disease, MND) at the ENCALS meeting, 18–20 May 2017, in Ljubljana, Slovenia.In May 2017, the US Food and Drug Administration (FDA) granted a license for the drug known as edaravone (licensed in Japan in 2015 as Radicut) for the treatment of ALS in the United States (to be marketed as Radicava). We are not aware of any official request from Mitsubishi Tanabe Pharma, the manufacturer of edaravone, to the European Medicines Agency (EMA) to register the drug for use in ALS in Europe. However, edaravone can be imported to Europe from Japan or the United States.The FDA approval of edaravone is based on a single positive clinical trial. The ENCALS neurologists were of the view that the outcome of this trial requires a balanced and considered interpretation when considering how best to advise those with ALS and their families. This study showed that edaravone may slow disease progression in ALS, but the disease-modifying effect was limited to a subgroup of ALS patients with distinct clinical characteristics. For ALS patients without those characteristics there is currently no evidence for a therapeutic benefit of edaravone.
Keywords: Amyotrophic lateral sclerosis (ALS); Edaravone